Making Tool Equipment for Quality Standard of Hydraulic Cylinder Remanufacturing in PT UTR - Manurung, Vuko Arief Tua; Febriyanto, Reza Candra; Wibowo, Yohanes Trijoko (International Journal Labs, 2023)
This paper deals with process of remanufacturing which is a process that is applied to products have expired or have been damaged, so the products can be reused with almost the same quality and balance as new products. PT UTR plant Jakarta has a new project, namely remanufacturing PT MCG's hydraulic cylinder. To maintain customer trust, each component that is remanufacturing must be ensured of its quality by means of testing before being sent to the customer. This equipment is made based on the use of management methods that have been standardized, namely 7++ ups tools. In collecting the required data, a direct approach was taken by following the existing remanufacturing process flow, so that the tool to be made was really useful and easy to use. From the results of the research carried out, we make a special equipment of a stand test bench hydraulic cylinders so that each component of the hydraulic cylinder that was remanufacturing could be done on a test bench. With this equipment, the quality standards of remanufacturing hydraulic cylinders can be accounted for.